Brand Value in Social Interaction - Kuksov, Dmitri (Management Science, 2007)
This paper explores the consumer value of publicly associating oneself with a brand image. The economic value of such association to the consumer of a brand is coming from its affect on the information exchange between consumers engaged in a search for partnerships with each other. It turns out that the brand use can be valuable to consumers for communication even when they do not have the proper incentives to make simple conversations valuable or informative. In particular, when the correlation of the interests of agents in a partnership is low, conversations are not very informative, while brand use remains informative and valuable. Furthermore, the more widespread the brand use is, the less truthful (and informative) one can expect conversations to be. In addition, the consumer value of a brand image is shown to have an inverse-U shape in the difficulty of searching, as consumers look for conformity when a search is difficult, and conversations become more and more truthful when a search becomes very easy.